Thermodynamic and Kinetic Characteristics of Nitrogen Hydrates Respond to Thermo-Analytical Technique - Chen, Qiang; Liu, Changling; Ye, Yuguang (Asian Journal of Chemistry, 2014)
In this study, a high pressure differential scanning calorimetry, based upon a thermo-analytical technique, was applied in order to investigate the kinetic and thermodynamic characteristics of nitrogen hydrates. The phase equilibrium conditions and the dissociation heat were determined by analyzing the endothermic heat flow curves during the hydrate dissociation process. In the nucleation stage, exothermic heat flow curves provided a lot of information about the kinetics, such as sub-cooling, nucleation time and the growth speed of hydrates crystals. In the bulk phase system, sub-cooling played an important part in the formation process of hydrates. However, other factors, such as the gas supply method, as well as the limitations that are inherent to the experimental apparatus also affected the reaction. It seems that, unlike the relatively stable behaviour in dissociation, hydrate nucleation and formation rely upon a probabilistic scheme.